KONSTRUKSI SOSIAL DALAM JALINAN HUBUNGAN FRIENDS WITH BENEFITS (STUDI PADA ANAK MUDA DI KOTA MANADO) - Diana Sucitra, Imelda; Pratiknjo, Maria Heny; Kawung, Evelin J.R (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research explores the social construction within the "Friends with Benefits" (FWB) relationships among young people in the city of Manado. Employing a qualitative method involving in-depth interviews and participatory observation, the study reveals that the FWB concept extends beyond the physical dimension, encompassing emotional and social aspects. Young individuals in FWB relationships in Manado tend to construct the meaning and boundaries of these relationships in alignment with local cultural values. Within the dynamics of FWB, adjustments and reinterpretations of existing social norms are evident, creating a space acceptable within society. The ambiguity in FWB relationship boundaries highlights the ongoing process of social construction, reflecting the dynamics of modern young interpersonal relationships. These findings provide profound insights into the complexity of social constructions in FWB within the local cultural context, emphasizing the importance of understanding shifts in norms and values in interpersonal relationships.